Effect of Ni Content Variation on the Synthesis of Nickel-Mobile Crystalline Material-41 (Ni-MCM-41) for Methylene Blue Adsorption - L. O. Ahmad; H. Hidayat; A. Zaeni; F. Muhamad (International Journal of Acta Material, 2025)
The research studied the enhancement of thermal resistance and the increase of adsorption capacity of methylene blue dye by Ni-doped mesoporous MCM-41 adsorbent (Ni-MCM-41). Ni-MCM41 were prepared using hydrothermal method with variation of Ni content ratio (Si/Ni = 10, 20, and 40). This study consisted of several stages including; preparation of 0.24 M sodium 1-heptansulphonate, nickel sulphate 0.025 M, 0.05 M and 0.1 M and 1 M sodium silicate solutions. Synthesis of Ni-MCM-41 which was characterized using FTIR, XRD, DSC and BET. The adsorption process experiments included the preparation of mother liquor and methylene blue standard solution, preparation of standard solution and determination of maximum wavelength, preparation of test solution, contact time variation and concentration variation. Wavelength, contact time variation and concentration variation were determined using UV-Vis spectrophotometer. Analyze the adsorption process by determining the percentage and maximum capacity of adsorption. As well as determining the type of adsorption that occurs through Freundlich and Langmuir adsorption isotherms. FTIR results showed wave numbers between 3400-3200 cm-1 indicating the presence of Si-OH groups, C-H group stretching vibrations at 2925 cm-1, asymmetric stretching vibrations of Si-O at 1239 cm-1, Si-O-Ni bending vibrations at 557 cm-1 and symmetric and asymmetric Si-O-Si stretching vibrations at 1081 cm-1. XRD showed the characteristic structure of MCM-41 with higher crystallinity obtained at Ni-MCM-41 ratio (Si/Ni=40), DSC showed greater thermal resistance of Ni-MCM-41 ratio (Si/Ni=40) at 175.13 oC. The adsorption capacity of methylene blue dye by MCM-41 and Ni-MCM-41 ratio (Si/Ni=40) were 4.0322 mg/g and 4.2735 mg/g, respectively, following Langmuir adsorption isotherm.